Upaya Mengenalkan Hadits Pada Anak Usia 5-6 Tahun Melalui Metode Gerakan Tangan - Hanita Hanita; Yahdinil Firda Nadhirah; Muhiyatul Huliyah; Juhri Juhri (As-Sibyan, 2022)
The lack of teacher ability in using the method causes children to have difficulty remembering the hadith that has been taught. The author conducted classroom action research (CAR) introducing hadith through the hand movement method carried out at RA Ar-Rohmah Serang City on 7 children’s. CAR was carried out in 2 cycles using the Kemmis and MC Taggart models and was descriptive qualitative. The results of the CAR carried out obtained 66,07% in cycle 1 with the criteria of Developing According to Expectations (DAE) and in the second cycle it rose to 86,16% with the criteria of Very Good Development (VGD), thus the hand movement method can improve children’s ability to recognize hadith.